Ensuring Favourable Taxing Rights for Business Profits : An Appraisal of the Permanent Establishment Concept in the UN and OECD Model Tax Conventions - Oguttu, Annet Wanyana (University of Pretoria, 2020)
Mini Dissertation (MCom)--University of Pretoria, 2019.